1994
DOI: 10.1139/y94-020
|View full text |Cite
|
Sign up to set email alerts
|

Cold cardioplegia and the K+ channel modulator aprikalim (RP 52891): improved cardioprotection in isolated ischemic rabbit hearts

Abstract: Cellular potassium extrusion is now considered a natural protective mechanism following myocardial ischemia, and newly synthetized molecules mimicking cellular extrusion of K+ (potassium channel activators) appear promising for cardioprotection, although the underlying mechanisms for their beneficial effects have not been fully characterized. Indeed, the cardioprotective efficacy of K+ channel activators at low temperature or in the presence of the high K+ content of standard cardioplegic solution has never be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 17 publications
1
22
0
Order By: Relevance
“…While depolarizing cardioplegic solutions are efficacious, further increases in protection during the bypass procedure would be useful. Previous studies indicated that KAT, openers either have a small additional protective effect when combined with depolarizing cardioplegia or no additional effect (10,26). It was not apparent in these studies if the high potassium-containing cardioplegic solutions effectively abolished the pharmacologic activity of the KATp openers by attenuating the electrochemical gradient, although the study by Pignac et al (26) suggested some efficacy.…”
Section: In Vitro Cardioprotective Profilementioning
confidence: 87%
“…While depolarizing cardioplegic solutions are efficacious, further increases in protection during the bypass procedure would be useful. Previous studies indicated that KAT, openers either have a small additional protective effect when combined with depolarizing cardioplegia or no additional effect (10,26). It was not apparent in these studies if the high potassium-containing cardioplegic solutions effectively abolished the pharmacologic activity of the KATp openers by attenuating the electrochemical gradient, although the study by Pignac et al (26) suggested some efficacy.…”
Section: In Vitro Cardioprotective Profilementioning
confidence: 87%
“…Pharmacological studies suggest a role for I KATP channels, [97][98][99] although the consensus has been that preconditioning results from activation of mitochondrial, 100 not sarcolemmal, I KATP channels. [101][102][103][104] In Langendorff perfused Kir 6.2 Ϫ/Ϫ hearts, however, the protective effect of preconditioning is abolished in spite of the fact that the infarction resulting from ( The application of transgenic and targeted deletion strategies in mouse has led to the identification of the ␣ subunits contributing to the formation of most of the K ϩ channels expressed in cardiac cells (Tables 1 and 2).…”
Section: In Sur2mentioning
confidence: 99%
“…In this situation, the action potential shortening is accelerated, leading to a decrease in amplitude of intracellular Ca 2+ diffusion and Ca 2+ overload. 3,4 In this study, the K + ATP-dependent channel opener, aprikalim, can significantly prolong cardiac allograft survival compared to the control group. This protective effect may be caused by vasodilation and/or cardiac protection.…”
Section: Discussionmentioning
confidence: 71%
“…They play a major role in vascular tone, 2 in cardiac depolarization, 3,4 and in insulin secretion. 5 Confirmation that ion channels are implicated in T-lymphocyte activities has been reported and transmembrane movement plays a critical role in lymphocyte activities.…”
Section: Microsurgery 19:314-317 1999mentioning
confidence: 99%